A Method of Linear Controller Gain Scheduling for Nonlinear Process Control - Levisauskas, D. (Elektronika ir Elektrotechnika, 1999)
A method of a linear controller gain scheduling for set-point control of a single input single output nonlinear process is presented. Application of the method refers on a presumption that the process state model is available and the state variables are measured or estimated on-line. The method is based on exploiting a transfer function of the controlled process derived from the state model. The transfer function is up-dated on-line with the estimates of state variables and is applied for real-time setting of a linear controller parameters. Efficiency of the method is investigated by simulation and realization the control of extremely nonlinear technological processes.